Pengaruh Leverage, Profitabilitas, Dan Arus Kas Operasi Terhadap Earning Per Share Pada Perusahaan Property dan Real Estate Yang Terdaftar Di Bursa Efek Indonesia Periode 2017-2019 - solikhul hidayat; Dian Mutia Maryani; Moch Aminnudin (Accounting Study Program, Faculty of Economics and Business, 2023)
This study aims to determine how much earning per share or earnings per share given by the company which is calculated from the leverage, profitability and operating cash flow. This study uses three independent variables consisting of leverage, profitability and operating cash flow and the dependent variable, namely earnings per share. This type of research is quantitative research. The population in this study were property and real estate companies listed on the Indonesia Stock Exchange for the period 2017-2019. The sampling technique used was purposive sampling method and the data analysis method used was the classical assumption test, hypothesis test and multiple linear regression using the SPSS 25 assistance program.The results showed that the profitability had a positive and significant effect on earnings per share. Meanwhile, leverage and operating cash flow have no effect on earnings per share